Zero, one, or in between: Evaluation of alternative national and entity-level accounting for bioenergy - Bird, D.N.; Pena, N.; Zanchi, G. (2011)
Accounting for bioenergy's carbon dioxide (CO2) emissions, as done under the Kyoto Protocol (KP) and European Union (EU) Emissions Trading Scheme, fails to capture the full extent of these emissions. As a consequence, other approaches have been suggested. Both the EU and United States already use value-chain approaches to determine emissions due to biofuels – an approach quite different from that of the KP. Further, both the EU and United States are engaged in consultation processes to determine how emissions connected with use of biomass for heat and power will be handled under regulatory systems. The United States is considering whether CO2 emissions from biomass should be handled like fossil fuels. In this context, this article reviews and evaluates the three basic bioenergy accounting options.* CO2 emissions from bioenergy are not counted at the point of combustion. Instead emissions due to use of biomass are accounted for in the land-use sector as carbon stock losses – a combustion factor (CoF) = 0 approach; * CO2 emissions from bioenergy are accounted for in the energy sector – a CoF = 1 approach; and * End users account for all or a specified subset of CO2 emissions, regardless of where geographically these emissions occur – 0 < CoF < 1. Following short descriptions of the basic options, this article discusses variations to these options and uses numerical examples to illustrate the impacts of approaches at a local and international level. Finally, the alternative accounting systems are evaluated against general criteria and for impacts on selected stakeholder goals. General criteria considered are: (a) comprehensiveness, (b) simplicity, and (c) scale independence. Stakeholder goals reviewed are: (a) stimulation of rural economies, (b) food security, (c) GHG reductions, and (d) preservation of forests.